Perceived challenges and attitudes to regimen and product selection from Italian haemophilia treaters: the 2013 AICE survey. (March 2014) - Franchini, M.; Coppola, A.; Rocino, A.; Zanon, E.; Morfini, M.; ,
Summary: Despite great advances in haemophilia care in the last 20 years, a number of questions on haemophilia therapy remain unanswered. These debated issues primarily involve the choice of the product type (plasma‐derived vs. recombinant) for patients with different characteristics: specifically, if they were infected by blood‐borne virus infections, and if they bear high or low risk of inhibitor development. In addition, the most appropriate treatment regimen in non‐inhibitor and inhibitor patients compel physicians operating at the haemophilia treatment centres (HTCs) to take important therapeutic decisions, which are often based on their personal clinical experience rather than on evidence‐based recommendations from published literature data. To know the opinion on the most controversial aspects in haemophilia care of Italian expert physicians, who are responsible for common clinical practice and therapeutic decisions, we have conducted a survey among the Directors of HTCs affiliated to the Italian Association of Haemophilia Centres (AICE). A questionnaire, consisting of 19 questions covering the most important topics related to haemophilia treatment, was sent to the Directors of all 52 Italian HTCs. Forty Directors out of 52 (76.9%) responded, accounting for the large majority of HTCs affiliated to the AICE throughout Italy. The results of this survey provide for the first time a picture of the attitudes towards clotting factor concentrate use and product selection of clinicians working at Italian HTCs.